2005
DOI: 10.1073/pnas.0407827102
|View full text |Cite
|
Sign up to set email alerts
|

Global energy gradients and size in colonial organisms: Worker mass and worker number in ant colonies

Abstract: Body mass shapes processes from cell metabolism to community dynamics. Little is known, however, about how the average body mass of individuals varies among ecological communities. Ants alter colony mass by independently changing worker mass and͞or worker number. In a survey of 49 ecosystems from tundra to tropical rainforest, average worker mass and worker number were uncorrelated (rs ‫؍‬ 0.2, P > 0.14) and varied 100-fold. Data supported the hypothesis that higher mean monthly temperatures, T, reduce worker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 63 publications
0
71
0
1
Order By: Relevance
“…of a small bird [19]; indeed, the body of T. lubei is larger than that of a rufous hummingbird (figure 3d ). Although the average size of workers within modern ant communities tends to increase with latitude [36,37], almost all of the largest individual living ant species (any caste 3 cm long) inhabit tropical regions with MAT over 208C ( figure 4a,b). They are scattered among subfamilies, have differing castes as the largest achieve great size by different morphologies and are widely separated on different continents.…”
Section: Discussion (A) the Status Of Formiciine Speciesmentioning
confidence: 99%
“…of a small bird [19]; indeed, the body of T. lubei is larger than that of a rufous hummingbird (figure 3d ). Although the average size of workers within modern ant communities tends to increase with latitude [36,37], almost all of the largest individual living ant species (any caste 3 cm long) inhabit tropical regions with MAT over 208C ( figure 4a,b). They are scattered among subfamilies, have differing castes as the largest achieve great size by different morphologies and are widely separated on different continents.…”
Section: Discussion (A) the Status Of Formiciine Speciesmentioning
confidence: 99%
“…5 colonies/m 2 , Kaspari 1996) of mostly small colonies (ca. 10-1000 workers, Kaspari 2005) that can relocate once every two weeks (Byrne 1994). There is evidence for strong responses of ant abundances to food supplements in this system, as shown by studies using bulk insect addition (McGlynn 2006, Shik and.…”
Section: Tropical Ant Communities As Subjects Of Bottom-up Experimentsmentioning
confidence: 99%
“…Many studies have shown the factors that determine the ant diversity in different spatial scales (Hölldobler & Wilson 1990, Andersen 1997, Cerdá 1997, Gibb & Hochuli 2002, Ribas et al 2003, Floren & Linsenmair 2005, Kaspari 2005). These factors act differently in different spatial scales and vegetation types (Santos et al 2006).…”
Section: Discussionmentioning
confidence: 99%